Myositis as initial presentation of sarcoidosis: A rarity - Mayank Gupta; Lalit Duggal; Neeraj Jain; Bhavya Chintala (Indian Journal of Rheumatology)
Sarcoidosis is a multisystem chronic inflammation characterized by noncaseating granulomas with internal organ involvement. Lung and lymph nodes are most commonly affected with muscles are involved in up to 3% of patients. Here, we discuss a 39-year-old male patient consulted in rheumatology OPD with chief complaints of localized swelling over the left calf since 6 months. Routine blood investigations were normal. Magnetic resonance imaging of the left thigh muscles was done which was suggestive of features of inflammatory myositis. Muscle biopsy was suggestive of epithelioid granulomas, more in favor of sarcoidosis. Contrast-enhanced computed tomography chest revealed symmetrical nodules in upper lobes of both lungs. We made a diagnosis of granulomatous myositis secondary to sarcoidosis. Steroids and azathioprine were started. The patient responded well to treatment and muscle swelling subsided.